Sustainable energy management - a prerequisite for the realization Kyoto Protocol - Mirjana Golušin; Olja Munitlak Ivanović; Simonida Vučenov (Journal of Economic Development, Environment and People, 2012)
Energy management can be defined as the process of planning, directing, implementing and controlling the process of generation, transmission and energy consumption. Energy management is a kind of synthesis of phenomena and concepts of modern energy management (management), or the use of modern settings management in the energy sector. Furthermore, when outlining the basic settings for power management Modern management is based on the assumptions of sustainability and conservation of energy stability for present and future generations. Therefore, modern energy management can be seen as a kind of synthesis of three actuarial sciences: energy, sustainable development and management. Sustainable Energy Management is a unique new concept, idea and approach that require many changes in the traditional way of understanding and interpretation of energy management at all levels. Sustainable energy management concept can not therefore be construed as an adopted and defined the concept, but must be constantly modified and adjusted in accordance with changes in the three areas that define it, and in accordance with the specific country or region where applicable. Accordingly, sustainable energy management can be defined as the process of energy management that is based on fundamental principles of sustainable development.